Systematics litrature review: development of ispring-assisted mathematics learning media to develop students' numeracy and digital literacy skills - Shodiq, Lukman Jakfar; Zuniawati, Serli; Marhaeni, Nafida Hetty (Universitas Mercu Buana Yogyakarta, 2024)
Numeracy literacy and digital literacy are two essential competencies that need to be developed in mathematics learning in the digital era. However, field evidence shows that both skills remain relatively low among Indonesian students. While various studies have explored the development of digital learning media to enhance one of these two aspects, there is still a limited number of studies that specifically integrate both into a single learning medium supported by interactive platforms such as iSpring. This study aims to review previous research findings through the Systematic Literature Review (SLR) method on the development of iSpring-assisted mathematics learning media in improving students’ numeracy and digital literacy skills. Data were collected from 24 selected relevant articles published between 2018 and 2024. Considering the limited findings that directly address the use of iSpring in this context, the study seeks to identify the extent to which iSpring-based learning media is valid and effective in supporting the enhancement of numeracy and digital literacy.